Single step, phase controlled, large scale synthesis of ferrimagnetic iron oxide polymorph nanoparticles by thermal plasma route and their rheological properties - Raut, Suyog A.; Mutadak, Pallavi R.; Kumar, Shiv; Kanhe, Nilesh S.; Huprikar, Sameer; Pol, Harshawardhan V.; Phase, Deodatta M.; Bhoraskar, Sudha V.; Mathe, Vikas L. (Journal of Magnetism and Magnetic Materials, 2018)
In this paper we report single step large scale synthesis of highly crystalline iron oxide nanoparticles viz. magnetite (Fe3O4) and maghemite (gamma-Fe2O3) via gas phase condensation process, where micron sized iron metal powder was used as a precursor. Selective phases of iron oxide were obtained by variation of gas flow rate of oxygen and hence partial pressure of oxygen inside the plasma reactor. Most of the particles were found to possesses average crystallite size of about 20-30 nm. The DC magnetization curves recorded indicate almost super-paramagnetic nature of the iron oxide magnetic nanoparticles. Further, iron oxide nanoparticles were analyzed using Raman spectroscopy, X-ray photoelectron spectroscopy and Mossbauer spectroscopy. In order to explore the feasibility of these nanoparticles for magnetic damper application, rheological studies have been carried out and compared with commercially available Carbonyl Iron (CI) particles. The nanoparticles obtained by thermal plasma route show improved dispersion which is useful for rheological applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; magnetic properties; Nano-crystalline materials; Rheological properties; Thermal plasma

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C